Asas Kebebasan Berkontrak Sebagai Dasar Perkembangan Perjanjian Di Indonesia - Tami Rusli (Law Faculty of Universitas Bandar Lampung, 2015)
The principle of freedom of contract (freedom of contract) contained in Paragraph 3 of Article 1338 of the Civil Code, provides that everyone bebasa create and determine the form and content of the original agreement meets the requirements of good faith and propriety, decency. The approach used is a normative juridical using secondary data, data analysis performed by means of qualitative analysis. The results showed that the development of the principle of freedom of contract was able to bring injustice because this principle can only achieve its objectives, namely to bring prosperity as optimally as possible, if the parties have equal bargaining power. Advice can be given development agreements based principle of freedom of contract must be followed by the establishment of the rule of law, so that the creation of order and justice.